Bahasa Inggris - Effendi, Yusli (UNUSA Press, 2019)
In contemporary global politics, apparently Islam has become synonymous with conflict, instability, and violence. These negative labels in minds of many people reinforce the perception that Islam remain not to correlate with, even hinder, the quest for world’s peace, security, and human development, the sixteenth goal of SDGs.  This paper aims to explore how Islam explains and understand human security by discussing Islamic values particularly on the concepts of societal security and sustainable development based on Indonesian Islamic society experience with special reference to Malang city. Reassessing how Islam serves as ideational factor for protecting people, this paper is an effort of enriching human security by incorporating religious paradigm, in particular Indonesian Islam, as an alternative paradigm in developing better understanding of the subject and development discourse.